2020
DOI: 10.16984/saufenbilder.629553
|View full text |Cite
|
Sign up to set email alerts
|

Using PSO and Genetic Algorithms to Optimize ANFIS Model for Forecasting Uganda’s Net Electricity Consumption

Abstract: Uganda seeks to transform its society from a peasant to a modern and largely urban society by the year 2040. To achieve this, electricity as a form of modern and clean energy has been identified as a driving force for all the sectors of the economy. For this reason, electricity consumption forecasts that are realistic and accurate are key inputs to policy making and investment decisions for developing Uganda's electricity sector. In this study, we present an ANFIS long-term electricity forecasting model that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The parameter optimization of the ANFIS method has been done by the PSO algorithm and genetic algorithm (GA). As a result of the study, GA-ANFIS showed the best prediction performance compared to PSO-ANFIS and MLR [14].…”
Section: Journal Of Artificial Intelligence and Systemsmentioning
confidence: 89%
See 1 more Smart Citation
“…The parameter optimization of the ANFIS method has been done by the PSO algorithm and genetic algorithm (GA). As a result of the study, GA-ANFIS showed the best prediction performance compared to PSO-ANFIS and MLR [14].…”
Section: Journal Of Artificial Intelligence and Systemsmentioning
confidence: 89%
“…Kasule and Ayan [14] developed an ANFIS model to predict Uganda's electricity consumption. The parameter optimization of the ANFIS method has been done by the PSO algorithm and genetic algorithm (GA).…”
Section: Journal Of Artificial Intelligence and Systemsmentioning
confidence: 99%
“…The ANFIS model is dependent on the Takagi-Sugeno inference system guided by the IF-THEN rule and stimulated as a five-layered neural network utilizing the FIS concept [48]. The number of membership functions and fuzzy rules play an important role in the design of ANFIS [49]. In comparison to Mamdani FIS, the Sugeno membership parameters are automatically selected [15].…”
Section: Adaptive Nero-fuzzy Inference System (Anfis)mentioning
confidence: 99%
“…A hybrid PSO‐ANFIS approach for short‐term forecasting of consumption in Portugal was developed in [51]. Using the same PSO‐ANFIS model and the GA‐ANFIS model, [52] showed a forecast of electricity consumption in Uganda. In addition, other fairly efficient models have been developed in particular by the author in [53] who developed a novel short‐term prediction based on a genetic algorithm for adaptive neuro‐fuzzy inference system (ANFIS).…”
Section: Introductionmentioning
confidence: 99%